The Chilean-Peruvian Integration and Development Committee: Approaches to Arica’s social and business world around the border - Álvarez Torres, Camila (Instituto de Estudios Internacionales, 2020)
This text analyzes the achievements of and obstacles faced by the Border Integration and Development Committee (Comité de Integración y Desarrollo Fronterizo - CIDF) on the Chilean-Peruvian border between 2012 and 2016 as a space of cross-border consultation. The strategies deployed by the social and business world in Arica are analyzed based on interaction with key stakeholders within and outside of the CIDF. Interviews were conducted with social, economic and state actors from Arica who exhibited different attitudes regarding the border and its institutional spaces for contacts. The authors conclude that the business association linked to transport and construction is reluctant to engage in cross-border contact, while the union linked to tourism service has developed in a way that is more open to engaging with their peers in Tacna in Peru. For its part, the social world has adopted an open, integrationist outlook.